2012 International Conference on Renewable Energies for Developing Countries (REDEC) 2012
DOI: 10.1109/redec.2012.6416705
|View full text |Cite
|
Sign up to set email alerts
|

Reactive sputtering DC magnetron-deposited TiO<inf>2</inf> thin films intended for photoelectrolysis of water for hydrogen production

Abstract: Because of its photoelectrochemical properties, titanium dioxide is an attractive material in photoelectrolysis of water for hydrogen production. Magnetron sputtering is a common and practicable technique that has been used to deposit TiO 2 thin films with homogeneous uniformity and reproducibility for various applications. This work deals with the growth of anatse titanium dioxide on indium tin oxide substrate using reactive sputtering DC magnetron method to use them in hydrogen production. In view of the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…35 The literature has shown that deposition of thin titanium films on glass of approximately 140 nm thick with similar annealing temperatures has resulted in an anatase surface phase consistent with this study. [36][37][38] However, most deposition studies rarely deposit films as thin as those used in this study. The conversion of amorphous titanium oxide to crystalline anatase could be attributed to several properties of the sputtering process, such as chamber pressure or temperature, which alter the properties of the oxide.…”
Section: Discussionmentioning
confidence: 99%
“…35 The literature has shown that deposition of thin titanium films on glass of approximately 140 nm thick with similar annealing temperatures has resulted in an anatase surface phase consistent with this study. [36][37][38] However, most deposition studies rarely deposit films as thin as those used in this study. The conversion of amorphous titanium oxide to crystalline anatase could be attributed to several properties of the sputtering process, such as chamber pressure or temperature, which alter the properties of the oxide.…”
Section: Discussionmentioning
confidence: 99%